STRATEGI PROMOTIF DAN PREVENTIF UNTUK PASIEN HIPERTENSI MELALUI PENGOLAHAN MENTIMUN DAN SELEDRI DI DESA JENGGAWAH - Roby Aji Permana (LPPM Universitas dr. Soebandi, 2026)
Hypertension remains a major public health problem in Jenggawah Village, where many adults and older people still have limited knowledge of its prevention and nonpharmacological management. This community outreach initiative was designed to enhance public awareness regarding hypertension while demonstrating the use of processed cucumber and celery as an auxiliary method for managing blood pressure. The program was implemented through health education, interactive discussion, hands-on demonstrations of cucumber and celery preparation, question-and-answer sessions, and health screening, with pre-test and post-test questionnaires used to evaluate knowledge changes. The results showed a clear improvement in participants’ understanding after the intervention, as more respondents moved from low and moderate knowledge categories to good and very good categories. The activity also increased community awareness of healthy lifestyle practices and the use of local plant-based resources as complementary support in hypertension management. In conclusion, this educational and practical approach was effective in strengthening knowledge and promoting preventive health behavior in the community